Summary report of a digestibility trial on Atlantic salmon in seawater - Koppe, Wolfgang; Lamborelle, Georges; Sutter, David (Zenodo, 2022)
This report provides a summary of a digestibility trial that Matís performed for Nordic Soya on Atlantic salmon in seawater. Funding: Nordic Soya